Time, justice, and urban nature: procedural barriers to multi-species flourishing - Josephine Gillespie; Dan Penny; Rebecca Hamilton (npj Urban Sustainability)
Abstract This paper explores the ways in which urban green and blue spaces are beset by problematic governing processes that reinforce an unrepresentative and unjust environmental narrative. In efforts to operationalise Nature Based Solutions this is problematic for, ultimately, law may act to ‘freeze’ the environmental narratives that shape our urban ecosystems. In many cases the results will not adequately recognise multiple species or provide an adequate basis to learn from the self-organised resilience of ecosystems with a long history in place. In this paper we use an Australian case study to demonstrate that a once extensive plant community that was extirpated over the past 150 years is now unknown and unrepresented in environmental law and policy, despite its value for Nature Based Solutions. We suggest that modest regulatory change can act as a vehicle for more-than-human representation within existing decision-making processes. Improved representation of disrupted and marginalised ecologies may achieve the functionality needed for effective Nature Based Solutions and allow urban ecologies to flourish.